PENGARUH MEREK DAN PERSEPSI KUALITAS TERHADAP PERSEPSI NILAI SERTA DAMPAKNYA PADA NIAT UNTUK MEMBELI ULANG (Studi Empiris Pada Produk Agar-agarSwallow Globe Brand). - Agung Setyo Tjahjono, 12.42.02.0030 (Jurnal Mahasiswa Pasca Sarjana, 2014)
Swallow Globe Brand is the brand of agar-agar powder products in packaging sachet with Swallow bird logo and an image of a globe with a golden yellow color map of the world, wrapped in packaging dominant yellow color. The product is a market leader for this type of gelatin products. Due to increasing competition in emerging markets some gelatin products with the packaging and the drawings that resemble Swallow Globe Brand products. As stamp